Erotyzm i kobieta w reklamie - Wojtkowiak, Klaudia (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The aim of this paper is to analyze erotica in advertising. The pivotal question is how to create the image of women in advertisements. Twenty four TV spots showing different products accompanied by femalehave been tested. Article characterizes advertising, describes image and role of women.